The Indigenous Peoples In ASEAN: Critical Analysis On Development Aggression - Torrejas, Dolly Cajes; Canta, Ashley Pauline Ricaforte; Salvaloza, Jay-Ar Gonzales; Bualat, Grace Magalzo (Center for Southeast Asian Social Studies (CESASS), 2023)
Indigenous peoples (IPs) constantly face challenges in terms of culture, land and human rights. The IPs are often the subjects of government and private corporations' resource extraction and development initiatives in their ancestral domains and territories, hence, development aggression. This paper aims to have a critical analysis of the existing development aggression experienced by the IPs within the ten (10) member-states of the Association of Southeast Asian Nations (ASEAN). The researchers contend that ASEAN and its member-states lack robust actions and efficiency in addressing development aggression. Employing a qualitative-descriptive approach, this study utilized the Key Informant Interview (KII) as the primary data, along with document review for secondary sources. This study argues that the development aggression continues to persist among the ASEAN member states as the majority of member states failed to recognize IPs, resulting in continued infringement of their rights. Moreover, the COVID-19 measures was utilized against IP communities and the constant advancement of extractive industries. Furthermore, it has been proven that both National policies and regional mechanisms confront considerable difficulties and need more legal frameworks in dealing with development aggression. The ASEAN member-states are not fully implementing customary rules and other international standards established by organizations such as the UN and the ILO. This study found that there are five (5) policies which may help protecting the IPs against development aggression. The development of Grievance Redress Mechanisms (GRMs) within the ASEAN Intergovernmental Commission on Human Rights (AICHR) specific for IPs and the inclusion of indigenous communities in income- generating projects developed in their ancestral lands and resources is the main one.